Epigenetic Modifications May Regulate the Activation of the Hypopharyngeal Gland of Honeybees (Apis Mellifera) During Winter - Wang, Kang; Liu, Zhen-guo; Lin, Zhe-guang; Yin, Ling; Gao, Fu-chao; Chen, Guo-hong; Ji, Ting (Frontiers in Genetics, 2020)
DNA methylation is an epigenetic modification primarily responsible for individual phenotypic variation. This modification has been reported to play an important role in caste, brain plasticity, and body development in honeybees (Apis mellifera). Here, we report the DNA methylation profile of honeybee hypopharyngeal glands, from atrophy in winter to arousal in the following spring, through the use of whole-genome bisulfite sequencing. Consistent with previous studies in other Apis species, we found low methylation levels of the hypopharyngeal gland genome that were mostly of the CG type. Notably, we observed a strong preference for CpG methylation, which were localized in promoters and exon regions. This result further indicated that, in honeybees, DNA methylation may regulate gene expression by mediating alternative splicing, in addition to silencing gene in promoter regions. After assessment by correlation analysis, we identified seven candidate proteins encoded by differentially methylated genes, including aristaless-related homeobox, forkhead box protein O, headcase, alpha-amylase, neural-cadherin, epidermal growth factor receptor, and aquaporin, which are reported to be involved in cell growth, proliferation, and differentiation. Hypomethylation followed by upregulated expression of these candidates suggested that DNA methylation may play significant roles in the activation of hypopharyngeal glands in overwintering honeybees. Overall, this study elucidates epigenetic modification differences in honeybee hypopharyngeal glands by comparing an inactive winter state to an aroused state in the following spring, which could provide further insight into the evolution of insect sociality and regulatory plasticity.